Absence of AMPKα2 accelerates cellular senescence via p16 induction in mouse embryonic fibroblasts. (February 2016) - Ding, Ye; Chen, Jie; Okon, Imoh Sunday; Zou, Ming-Hui; Song, Ping
Highlights: AMPKα2 deletion leads to cellular senescence. Deletion of AMPKα2 is associated with an induction in p16. Antioxidant partially decreases p16 and subsequent cell senescence. Knockdown of HMG box-containing protein 1 (HBP1) blocks the cellular senescence via p16 reduction. Abstract: Emerging evidence suggests that activation of adenosine monophosphate-activated protein kinase (AMPK), an energy gauge and redox sensor, delays aging process. However, the molecular mechanisms by which AMPKα isoform regulates cellular senescence remain largely unknown. The aim of this study was to determine if AMPKα deletion contributes to the accelerated cell senescence by inducing p16 INK4A (p16) expression thereby arresting cell cycle. The markers of cellular senescence, cell cycle proteins, and reactive oxygen species (ROS) were monitored in cultured mouse embryonic fibroblasts (MEFs) isolated from wild type (WT, C57BL/6J), AMPKα1, or AMPKα2 homozygous deficient (AMPKα1 −/−, AMPKα2 −/− ) mice by Western blot and cellular immunofluorescence staining, as well as immunohistochemistry (IHC) in skin tissue of young and aged mice. Deletion of AMPKα2, the minor isoform of AMPKα, but not AMPKα1 in high-passaged MEFs led to spontaneous cell senescence demonstrated by accumulation of senescence-associated-β-galactosidase (SA-β-gal) staining and foci formation of heterochromatin protein 1 homolog gamma (HP1γ). It was shown here that AMPKα2 deletion upregulates cyclin-dependent kinase (CDK) inhibitor, p16, which arrests cell cycle. Furthermore, AMPKα2 null cells exhibited elevated ROS production. Interestingly, knockdown of HMG box-containing protein 1 (HBP1) partially blocked the cellular senescence of AMPKα2-deleted MEFs via the reduction of p16. Finally, dermal cells senescence, including fibroblasts senescence evidenced by the staining of p16, HBP1, and Ki-67, in the skin of aged AMPKα2 −/− mice was enhanced when compared with that in wild type mice. Taken together, our results suggest that AMPKα2 isoform plays a fundamental role in anti-oxidant stress and anti-senescence.